Analisis Kinerja Organisasi Dinas Pasar Kota Semarang - Anila Primadara; Hardi Warsono; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Performance is the result of work that had attained by a person in a group or organization in accordance with the authority and responsibilities. Organizational performance is the achievement of results at the organizational level or unit of analysis. Performance on the level of the Organization related the objectives of the Organization, design, organization, and management of the organization. Dinas Pasar Kota Semarang which has a role as a provider of public services, especially in the field of the Stup and management of Traditional markets, serve the community by providing a safe market, comfortable, orderly, clean and healthy. Dinas Pasar Kota Semarang carrying out the Affair of local government in the field of management of traditional markets and street vendors based on the principle of autonomy and pembantuan tasks. The city of Semarang had the vision that embodies the modern traditional markets towards a prosperous society.The purpose of the research was to analyze the performance of the Dinas Pasar Kota Semarang. Analyzing the factors that support and hinder the performance of Dinas Pasar Kota Semarang. Organizational performance assessment of public views of 5 dimensions such as productivity, responsivity, responsibility, accountability and quality of service; and 3 factors that influence the organizational performance of Dinas Pasar Kota Semarang such as organizational structure, leadership and team work. This results of the study as a whole, the performance of the Organization could not be said to be optimal if seen from the 5 dimension of performance assessment organizations and 3 factors that influence organizational performance of Dinas Pasar Kota Semarang. On dimension of productivity and accountability proved still need any improvement.